Synthesis of 1,2,4-Trihalophenothiazin-3-ones and Their Conversion into (1,4)-Benzothiazino-(2,3-b)-phenothiazines - Ojha, K.G.; Kawadiya, Mahaveer; Jaisnghani, Neera; Mathur, Priyanka (Asian Journal of Chemistry, 2010)
1,2,4-Trihalophenothiazin-3-ones (III) were prepared by condensing 2-amino benzenthiols (I). with chloranil/bromanil (II) in 1 : 1 molar ratio. Compounds (III) were further condensed with the same or different 2-arninobenzenthiol (IV) which afforded 1,4- benzothiazino-(2,3-b )-phenothiazines (V).